Sosialisasi Pajak Penghasilan PPh Pasal 21 pada Generasi Muda Karanglo yang Memiliki Usaha di Kabupaten Bantul - Safna Aulia Putri; Rochmad Bayu Utomo (Jurnal Pelayanan Masyarakat, 2024)
Young entrepreneurs in Karanglo Hamlet, Bantul, face difficulties in understanding and fulfilling tax obligations related to Income Tax Article 21 (PPh 21). This community service aims to increase their understanding of tax obligations, especially how to calculate Income Tax Article 21, through interactive approaches such as discussions and simulations of tax calculations. The socialization method was carried out for three days, namely on November 1-3, 2024, by involving the young generation who have businesses in the region as the main target. Before the activity, participants showed a low level of understanding of taxation, but after the socialization, there was a significant increase in their ability to understand and calculate Income Tax Article 21. This result emphasizes the importance of tax education to create a young generation that is tax-compliant and supports state revenue.